PENGARUH KEMAMPUAN KERJA, MOTIVASI KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. ENVIROMATE TECHNOLOGY INTERNATIONAL PADA PROYEK PEMBANGUNAN CNG PLANT LOMBOK - MUHAMAD AHYAT; OKKY AFRIWAN; FITRIA IKA AGUSTINA; MAHYANI MAHYANI (GANEC SWARA, 2023)
This study aims to determine the effect of work ability, work motivation and work environment on the performance of PT Enviromate Technology International employees in the Lombok CNG Plant Development project. This type of research is a quantitative research with a cross-sectional research design. This study used a sample of 30 respondents. Sampling used a saturated sample, where the entire population was sampled. The test tool used is a questionnaire. From the results of this test, it can be concluded that work ability has a significant effect on employee performance with a significant t value of 0,033. Work motivation  also  has  a  significant  effect  on  employee  performance  with  a significant t value of 0,000. The work environment also has a significant effect on employee performance with a significant t value of 0,000.